Impact of dietary risk factors on cardiometabolic and cancer mortality burden among Korean adults: results from nationally representative repeated cross-sectional surveys 1998–2016 - Jo, Garam (Nutr Res Pract, 2020)
BACKGROUND/OBJECTIVES: Dietary factors are important contributors to cardiometabolic and cancer mortality. We examined the secular trends of nine dietary factors (fruits, vegetables, whole grains, nuts and seeds, milk, red meat, processed meat, sugar-sweetened beverages, and calcium) and the associated burdens of cardiometabolic and cancer mortality in Korea using representative cross-sectional survey data from 1998 to 2016. SUBJECTS/METHODS: Using dietary data from Korean adults aged ≥ 25 years in the Korea National Health and Nutrition Examination Survey (KNHANES), we characterized secular trends in intake levels. We performed comparative risk assessment to estimate the population attributable fraction and the number of cardiometabolic and cancer deaths attributable to each dietary factor. RESULTS: A total of 231,148 cardiometabolic and cancer deaths were attributable to nine dietary risk factors in Korea from 1998 to 2016. Suboptimal intakes of fruits and whole grains were the leading contributors. Although the intakes of fruits, vegetables, and whole grains moderately improved over time, the intake levels in 2016 (192.1 g/d, 225.6 g/d, and 10.9 g/d, respectively) remained far below the optimal levels. Deaths attributable to the low intakes of nuts and seeds (4.5 g/d), calcium (440.5 mg/d), and milk (37.1 g/d) and the high intakes of red meat (54.7 g/d), processed meat (4.7 g/d), and sugar-sweetened beverages (33.0 g/d) increased since 1998. Compared with older age groups (≥ 45 years), more unfavorable changes in dietary patterns were observed in the younger population aged 25–44 years, including more sharply increased intakes of processed meat. CONCLUSIONS: We observed improvement in the intakes of fruits, vegetables, and whole grains and unfavorable changes in the intakes of processed meat and sugar-sweetened beverages over the past few decades. Our data suggest that to reduce the chronic disease burden in Korea, more effective nutritional policies and interventions are needed to target these dietary risk factors.